Atomically dispersed nickel(I) on an alloy‐encapsulated nitrogen‐doped carbon nanotube array for high‐performance electrochemical CO₂ reduction reaction - Zhang, Tianyu (2023)
Single-atom catalysts (SACs) show great promise for electrochemical CO2 reduction reaction (CRR), but the low density of active sites and the poor electrical conduction and mass transport of the single-atom electrode greatly limit their performance. Herein, we prepared a nickel single-atom electrode consisting of isolated, high-density and low-valent nickel(I) sites anchored on a self-standing N-doped carbon nanotube array with nickel–copper alloy encapsulation on a carbon-fiber paper. The combination of single-atom nickel(I) sites and self-standing array structure gives rise to an excellent electrocatalytic CO2 reduction performance. The introduction of copper tunes the d-band electron configuration and enhances the adsorption of hydrogen, which impedes the hydrogen evolution reaction. The single-nickel-atom electrode exhibits a specific current density of −32.87 mA cm−2 and turnover frequency of 1962 h−1 at a mild overpotential of 620 mV for CO formation with 97% Faradic efficiency.